Jejunogastric Intussusception: an Unusual Cause of Haematemesis - Rahman, Mohibur; Hossain, Akram; Amin, Robed; Uddin, Nasir; Hossain, Tanvir; Saha, Anjan Kumar; Rahman, Arifur; Hossain, Tanvir (Journal of Medicine, 2010)
Intussusception most commonly occurs in children and is rare in adults, accounting for only 5% of all cases of intussusceptions. Intussusception following gastric surgery is an extremely rare postoperative complication. We present a case where following gastrojejunostomy with truncal vagotomy a retrograde intussusception of the efferent limb into the gastrojejunostomy stoma occurred. The intussusception was well visualized by upper GI endoscopy prior to surgery. Exploratory laparotomy was done within 24 hours after the onset of the symptoms. After resection of loop of intussusceptum, gastrojejunostomy and jejunoileostomy was done. Keywords: Intususception, Intestinal invagination, Jejunogastric intussusception DOI:10.3329/jom.v11i1.4282 J Medicine 2010: 11: 86-89